A Chelation Strategy for In-situ Constructing Surface Oxygen Vacancy on {001} Facets Exposed BiOBr Nanosheets - Wang, Xiao-jing; Zhao, Ying; Li, Fa-tang; Dou, Li-jun; Li, Yu-pei; Zhao, Jun; Hao, Ying-juan (Scientific reports, 2016)
Surface defect of nanomaterials is an important physical parameter which significantly influences their physical and chemical performances. In this work, high concentration of surface oxygen vancancies (SOVs) are successfully introduced on {001} facets exposed BiOBr nanosheets via a simple surface modification using polybasic carboxylic acids. The chelation interaction between carboxylic acid anions and Bi 3+ results in the weakness of Bi-O bond of BiOBr. Afterwards, under visible-light irradiation, the oxygen atoms would absorb the photo-energy and then be released from the surface of BiOBr, leaving SOVs. The electron spin resonance (ESR), high-resolution transmission electron microscopy (HRTEM) and UV–vis diffuse reflectance spectra (DRS) measurements confirm the existence of SOVs. The SOVs can enhance the absorption in visible light region and improve the separation efficiency of photo-generated charges. Hence, the transformation rate of adsorbed O 2 on the as-prepared BiOBr with SOVs to superoxide anion radicals (•O 2 − ) and the photocatalytic activity are greatly enhanced. Based on the modification by several carboxylic acids and the photocatalytic results, we propose that carboxylic acids with natural bond orbital (NBO) electrostatic charges absolute values greater than 0.830 are effective in modifying BiOBr.